2021
DOI: 10.1002/app.51955
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the accelerated thermal aging behavior of polyetherimide and lifetime prediction at elevated temperature

Abstract: Fire‐protective clothing are manufactured using heat and flame resistant fibers that are made of high‐performance polymers. These polymers exhibit a gradual reduction in their performance after long‐term exposure under various aging conditions. This study investigates the thermal aging behavior of a high‐temperature resistance polymer, polyetherimide (PEI), at elevated temperatures in air. Changes in the ultimate tensile strength (UTS), glass transition temperature, and surface properties are observed. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…The sacrificial polymers behave similarly to the outer shell fabrics of firefighters' protective garments when exposed to the ageing conditions of heat, UV light, and moisture [9][10]. The exposure to ageing conditions will initiate a degradation in the sacrificial polymer layer of the sensor, ultimately disrupting the conductivity of the conductive track [8].…”
Section: Introductionmentioning
confidence: 99%
“…The sacrificial polymers behave similarly to the outer shell fabrics of firefighters' protective garments when exposed to the ageing conditions of heat, UV light, and moisture [9][10]. The exposure to ageing conditions will initiate a degradation in the sacrificial polymer layer of the sensor, ultimately disrupting the conductivity of the conductive track [8].…”
Section: Introductionmentioning
confidence: 99%
“…As the air-gap thickness increased, flaking of the original filaments on the fiber surface occurred; this was due to incomplete fiber fracturing owing to uneven heating. 28 No significant changes in raw-filament fracturing or the fiber fracture openings were observed with increased airflow velocity. However, the experimental sample groups with added under-clothing airflow exhibited more raw filament breakage than the control group without additional airflow.…”
Section: Fabric Morphologymentioning
confidence: 95%
“…From the perspective of thermal decomposition, cross-linking, and molecular chain breakage occurs when polymers thermally age. 28 Initially, thermal aging mainly involves polymer cross-linking; as the temperature increases, the weak bonds in the polymer chains break first. This is followed by molecular chain breakage, which eventually causes fiber breakage.…”
Section: Fabric Morphologymentioning
confidence: 99%
“…The typical peaks of C=O vibration at 1776 and 1722 cm −1 , C-N stretching vibration at 1357 and 1238 cm −1 were attributable to the PEI fibrous network and the O-H peak at 3416 cm −1 is the characteristic peak of Ti 3 C 2 T x MXene nanosheets. [34][35] The microstructure of MXene/PEI fibrous network was also analyzed by 3D optical profiler, as detailed in Figure 1h. It is revealed that the MXene/PEI fibrous network was randomly distributed with microscopic protrusions, allowing for the construction of highly sensitive piezoresistive sensor.…”
Section: Preparation and Characterization Of Mxene/pei Piezoresistive...mentioning
confidence: 99%